A Pollen Diet Confers Ultraviolet-B Resistance in Phytoseiid Mites by Providing Antioxidants - Sugioka, Nariaki; Kawakami, Mari; Hirai, Nobuhiro; Osakabe, Masahiro (Frontiers in Ecology and Evolution, 2018)
Many plant-dwelling mites including phytophagous spider mites and predacious phytoseiid mites suffer lethal deleterious effects from solar ultraviolet-B (UVB; 280–315 nm wavelength) radiation. Phytoseiid species also often feed on pollen as an alternative food source. As pollen is frequently exposed to solar radiation, it is likely to contain compounds that protect germ cells from UVB radiation and radiant heat. If phytoseiid mites can obtain these protective compounds, pollen feeding may play a role in their adaptation to UVB. In this study, we compared the potential protective effects of tea pollen, peach pollen, and Tetranychus urticae mites as food items in Neoseiulus californicus. Egg hatchability and adult female survival after UVB irradiation were higher in pollen-fed than mite-fed N. californicus. The major protective effects of peach pollen and tea pollen were UVB shielding effects and antioxidant capacity, respectively, and these were derived from distinctive antioxidant components. The major antioxidant in peach pollen was tri-p-coumaroylspermidine, although its antioxidant capacity was relatively low; instead, it effectively absorbed UVB radiation. By contrast, the major antioxidants of tea pollen were catechin and epicatechin 3-gallate, which had high antioxidant capacities. Our results indicate that the protective antioxidant components in pollen improved UVB resistance in N. californicus, contributing to their adaptation to solar radiation.